0
$\begingroup$

I'm not sure how to start this PDE since the initial and boundary conditions are nonzero. May someone point me in the right direction?

This is the problem:

$$u_{tt} = u_{xx}$$ $$u(x,0) = \frac{1}{2+ \sin(x)}$$ $$u_t(x,0) = -\frac{\cos(x)}{(2+ \sin(x))^2}$$ $$u(0,t) = u(2\pi,t)= \frac{1}{2+ \sin(t)}$$

$\endgroup$
0

2 Answers 2

0
$\begingroup$

Hint: The general solution of the 1D wave equation is $u(x,t)=F(x+t)+G(x-t)$.

$\endgroup$
4
  • $\begingroup$ Could you give a little more detail on how to use this formula? $\endgroup$ Jan 20, 2021 at 23:56
  • $\begingroup$ Insert the boundary conditions and figure out what $F,G$ must be. $\endgroup$ Jan 21, 2021 at 1:24
  • $\begingroup$ I got $$u(x,t)= \frac{1}{2+\sin(x+t)}$$ for $$x > t$$. Is that right? $\endgroup$ Jan 21, 2021 at 4:01
  • $\begingroup$ That's what I found too, though I don't see the need for $x>t$. (As a similar exercise, one can instead apply D'Alembert's formula. But said formula is derived from the above general solution so it's not actually different.) $\endgroup$ Jan 21, 2021 at 4:31
0
$\begingroup$

Firstly, you should get homogenous boundary conditions. Let $v(x, t) = \frac{1}{2+ \sin(t)}$. We will seek the solution in the form $u(x, t) = v(x, t) + w(x, t)$, so $w(x, t) = u(x, t) - v(x, t)$. After substitution $u$ into equation, we get $\partial_t^2 w - \partial_x^2 w = -\frac{4 \sin (t)+\cos (2 t)+3}{2 (\sin (t)+2)^3}$. In this case, the initial conditions will take the form $w(x, 0) = u(x, 0) - v(x, 0) = \frac{1}{2+ \sin(x)} - \frac{1}{2}$ and $\partial_t w(x, 0) = \partial_t u(x, 0) - \partial_t v(x, 0) = -\frac{\cos(x)}{(2+ \sin(x))^2} + \frac{1}{4}$, and the boundary conditions $w(0, t) = w(2 \pi, t) =0$. We will find $w$ as $w = y + z$, where

$$\partial_t^2 y - \partial_x^2 y = 0, y(x, 0) = \frac{1}{2+ \sin(x)} - \frac{1}{2}, \partial_t y(x, 0) = -\frac{\cos(x)}{(2+ \sin(x))^2} + \frac{1}{4}, y(0, t) = y(2 \pi, t) =0$$ $$\partial_t^2 z - \partial_x^2 z= -\frac{4 \sin (t)+\cos (2 t)+3}{2 (\sin (t)+2)^3}, z(x, 0) = \partial_t z(x, 0) = z(0, t) = z(2 \pi, t) =0$$

These functions can be found using separation of variables method.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.